2003
DOI: 10.3143/geriatrics.40.368
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of factors concerning the short-term outcome of elderly patients beginning dialysis

Abstract: The aim of the present study is to clarify relevant factors concerning the short-term outcome of elderly patients beginning dialysis. One hundred nineteen patients aged 60 years and over who had newly started dialysis at our hospital were studied. The male/female ratio was 70:49. The age was 74 +/- 7 years (mean +/- standard deviation). In all patients, the timing of referral to a nephrologist (early/late), the urgency of the initiation of dialysis (non-urgent/urgent), the cause of renal failure (nondiabetes/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In contrast in North America, the UK and other developed countries, the most common reason for death was withdrawal from the dialysis treatment 15–17 . Fujimaki found that the need for urgent dialysis was less among the ER cases compared with the LR cases 18 . We could not find any similar study conducted in Turkey regarding this phenomenon.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast in North America, the UK and other developed countries, the most common reason for death was withdrawal from the dialysis treatment 15–17 . Fujimaki found that the need for urgent dialysis was less among the ER cases compared with the LR cases 18 . We could not find any similar study conducted in Turkey regarding this phenomenon.…”
Section: Discussionmentioning
confidence: 71%
“…[15][16][17] Fujimaki found that the need for urgent dialysis was less among the ER cases compared with the LR cases. 18 We could not find any similar study conducted in Turkey regarding this phenomenon.…”
Section: Discussionmentioning
confidence: 80%
“…Frimat et al (11) found that the commencement of dialysis in an emergency was associated with late referral. Fujimaki et al also showed an increased need for urgent initial dialysis in late referrals (12). In our study, the maximum number of complications occurred during the first three months of follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Fujimaki and Kasuya studied 119 patients older than 60 years of age (mean age = 74 years) and showed increased need for urgent initiation of dialysis in late referred patients 10 . Urgent dialysis was associated with increased mortality.…”
Section: What Is the Evidence?mentioning
confidence: 99%